Penanggulangan Dampak Riba Melalui Pendekatan Pendidikan - Shidiq, Sapiudin (Prodi Pendidikan Agama Islam, 2018)
The usury is more and more act violently and arbitrarily in society. Its effect not only damages the economic system but also damages the mentality of agent. The  pressing, egoism and individulism are sign of the usury   badness. If its current can't be minimalized, the usury  will cause  to collapse  the society  harmony. Clearly, Islam  forbids the usury. The function of Islamic education is doing  preventif and kuratif stride